Externalizing behavior and substance use related problems at 15 years in prenatally cocaine exposed adolescents. Issue 3 (15th February 2014) - Min, Meeyoung O.; Minnes, Sonia; Lang, Adelaide; Weishampel, Paul; Short, Elizabeth J.; Yoon, Susan; Singer, Lynn T.
ABSTRACT: The effect of prenatal cocaine exposure (PCE) on externalizing behavior and substance use related problems at 15 years of age was examined. Participants consisted of 358 adolescents (183 PCE, 175 non‐cocaine exposed (NCE)), primarily African–American and of low socioeconomic status, prospectively enrolled in a longitudinal study from birth. Regression analyses indicated that the amount of PCE was associated with higher externalizing behavioral problems ( β = .15, p = .02). Adolescents with PCE were also 2.8 times (95% CI = 1.38–5.56) more likely to have substance use related problems than their NCE counterparts. No differences between PCE adolescents in non‐kinship adoptive/foster care ( n = 44) and PCE adolescents in maternal/relative care ( n = 139) were found in externalizing behavior or in the likelihood of substance use related problems. Findings demonstrate teratologic effects of PCE persisting into adolescence. PCE is a reliable marker for the potential development of problem behaviors in adolescence, including substance use related problems.